Pengaruh Citra Merek, Persepsi Kualitas, Social Media Influencers Terhadap Minat Beli Produk Skincare MS Glow (Studi Kasus Wanita Malang) - Aisyah Wulandari; Achmad Agus Priyono; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
AbstractThis study aims to identify the effects of brand image, quality perception, and social media influencers on purchasing intentions. Quantitative research was the method used in this investigation. Probability sampling or simple random sample is the technique used in sampling. By multiplying the number of indicators by 5 as part of the sampling process, 80 respondents are produced. The findings of this study demonstrate that brand image, quality perception, and social media influencers all significantly influence consumers' willingness to make a purchase.  Keywords: Brand Image, Quality Perception, Social Media Influencers, Buying Interest